Influence of Coordination and Strategic Planning on Organizational Performance with Change Management Mediating Variables in the Era of Volatility, Uncertainty, Complexity and Ambiguity (VUCA) - Agus Puji Widodo CK; Yandra Arkeman; Anny Ratnawati; Idqan Fahmi (LPPM Universitas PGRI Sumatera Barat, 2023)
Strategic management functions are elements that are always attached to the management process which will be used as a reference in carrying out activities or structured planning to achieve predetermined goals. This research aims to design a change management model for organizational performance at government institution XYZ in an era of volatility, uncertainty, complexity and ambiguity (VUCA). The social theory used in this research is Marxian theory, the name for several theoretical explanations inspired by Karl Marx. The emphasis in Marxian theory is that old assumptions such as the opposition of two large classes, the bourgeoisie and the proletariat, inspire explanations of modern phenomena. Research data was obtained by filling out an online questionnaire by 207 employees of the XYZ government agency. The sampling method used was purposive sampling. The variables used in this research are coordination, strategic planning, change management, and organizational performance. The influence of coordination, strategic planning and change management variables on organizational performance will be modeled using a structural equation model. The results show that there is a positive influence of coordination, strategic planning and change management variables on organizational performance. Change management variables are proven to fully mediate the influence of coordination and strategic planning on organizational performance. Its effectiveness can be seen from coordination and strategic planning which cannot significantly influence organizational performance without the mediating variable of change management. The findings of this paper have academic, managerial, and policy implications that can provide a theoretical foundation for future research in measuring and managing organizational sustainability performance and contribute to knowledge in the field of performance measurement.